Impact of heavy metal and pesticide contamination in water and soil on hemoglobin synthesis and lymphocyte counts - Artati Artati; Nuradi Nuradi; Herman Herman; Asyhari Asyikin; Nurisyah Nurisyah; Ratnasari Dewi; Rafidah Rafidah; Aan Yulianingsih; Asriyani Ridwan (Institute of Advanced Engineering and Science, 2026)
Heavy metal and pesticide pollution represent a significant public health concern, particularly due to their detrimental effects on hematological health. This study investigates the levels of heavy metals, specifically lead (Pb), cadmium (Cd), and arsenic, and organophosphate pesticides in water and soil within five sub-districts of Jeneponto City, utilizing a quantitative descriptive analysis methodology with the simple random sampling over a six-month period. Analytical techniques employed include atomic absorption spectrophotometry (AAS) for heavy metals and UV-Vis spectrophotometry for pesticides, complemented by blood analyses for hemoglobin and lymphocyte counts. Results reveal that soil samples exhibited heavy metal concentrations exceeding regulatory thresholds, with copper (Cu) and Cd identified as particularly concerning. While most organophosphate pesticide levels were below established limits, concerns regarding potential residue accumulation persist. Exposure to these pollutants has been linked to disrupted hematopoiesis and immune system impairments, potentially resulting in anemia and heightened vulnerability to infections. This study underscores the critical need for continuous monitoring of heavy metal and pesticide levels in environmental matrices to mitigate adverse health outcomes and protect ecosystems. Regular assessments are vital for public health policy and environmental management strategies.